IL-2 is involved in immune response of prenatally stressed rats exposed to postnatally stimulation - Falcone, Eliana G; Liaudat, Ana C; Alustiza, Fabrisio E; Mayer, Nora; Bosch, Pablo; Vivas, Adriana; Gauna, Hector; Rodríguez, Nancy (Austral Journal of Veterinary Sciences, 2017)
Environmental cues influence growth and development of mammals during prenatal and particularly early postnatal life and can exert long-lasting effects in adult life. High circulating concentration of glucocorticoids during pregnancy (prenatal stress) affects the activity of the hypothalamic-pituitary-adrenal axis (HPA) of offspring and has been linked to alter immune system responses. Early postnatal stimulation (handling) of prenatally stressed animals generates long-term beneficial effects on the reactiveness of the HPA axis and immune system function. The aim of this study was to further investigate the effect of handling on immune response in prenatally stressed male rats and to elucidate a possible relationship with the HPA axis activity. Control and prenatally stressed (PS) offspring by immobilization (IMO) were handled during the first week of life. Animals from both treatments were subjected to acute stress by IMO. Corticosterone (COR) plasma concentration was measured by RIA assay, T lymphocyte proliferation by [3H] thymidine assay and IL-2 levels by direct ELISA technique. Chronic IMO prenatal stress caused an increase in mother plasma COR basal levels. Furthermore, prenatally stressed rats subjected to an acute stress session had lower T cell proliferation and decreased IL-2 release. In addition, early postnatal stimulation reversed the negative effects of prenatal stress on proliferation of T lymphocytes and IL-2 release.